Ataluren-Promising Therapeutic Premature Termination Codon Readthrough Frontrunner - Sylwia Michorowska (MDPI AG, 2021)
Around 12% of hereditary disease-causing mutations are in-frame nonsense mutations. The expression of genes containing nonsense mutations potentially leads to the production of truncated proteins with residual or virtually no function. However, the translation of transcripts containing premature stop codons resulting in full-length protein expression can be achieved using readthrough agents. Among them, only ataluren was approved in several countries to treat nonsense mutation Duchenne muscular dystrophy (DMD) patients. This review summarizes ataluren's journey from its identification, via first in vitro activity experiments, to clinical trials in DMD, cystic fibrosis, and aniridia. Additionally, data on its pharmacokinetics and mechanism of action are presented. The range of diseases with underlying nonsense mutations is described for which ataluren therapy seems to be promising. What is more, experiments in which ataluren did not show its readthrough activity are also included, and reasons for their failures are discussed.